Fluoroquinolone exposure in utero did not affect articular cartilage of resulting foals. (20th July 2020) - Ellerbrock, Robyn E.; Canisso, Igor F.; Larsen, Ryan J.; Garrett, Katherine S.; Stewart, Matthew C.; Herzog, Kalyn K.; Kersh, Mariana E.; Moshage, Sara G.; Podico, Giorgia; Lima, Fabio S.; Childs, Bronwen A.
Abstract: Background: Recent studies have shown that fluoroquinolones, specifically, enrofloxacin and its active metabolite (ciprofloxacin), cross the equine placenta without causing gross or histological lesions in the first and third trimester fetuses or resulting foal. However, it is possible that in utero exposure to fluoroquinolones may cause subtle lesions not detectable by standard means; thus, a more in‐depth assessment of potential toxicity is warranted. Objectives: To use quantitative magnetic resonance imaging (qMRI), biomechanical testing, and chondrocyte gene expression to evaluate the limbs of foals exposed to enrofloxacin during the third trimester of pregnancy. Study design: In vivo and control terminal experiment. Methods: Healthy mares at 280 days gestation were assigned into three groups: untreated (n = 5), recommended therapeutic (7.5 mg/kg enrofloxacin, PO, SID, n = 6) or supratherapeutic (15 mg/kg, PO, SID, n = 6) doses for 14 days. Mares carried and delivered to term and nursed their foals for 30 days. Two additional healthy foals born from untreated mares were treated post‐natally with enrofloxacin (10 mg/kg PO, SID, for 5 days). By 30 days, foal stifles, hocks, elbows, and shoulders were radiographed, foals were subjected to euthanasia, and foal limbs were analysed by quantitative MRI, structural MRI, biomechanical testing and chondrocyte gene expression. Results: Osteochondral lesions were detected with both radiography and structural MRI in foals from both enrofloxacin‐treated and untreated mares. Severe cartilage erosions, synovitis and joint capsular thickening were identified in foals treated with enrofloxacin post‐natally. Median cartilage T2 relaxation times differed between joints but did not differ between treatment groups. Main limitations: A small sample size was assessed and there was no long‐term follow‐up. Conclusion: While further research is needed to address long‐term foal outcomes, no differences were seen in advanced imaging, biomechanical testing or gene expression by 30 days of age, suggesting that enrofloxacin may be a safe and useful antibiotic for select bacterial infections in pregnant mares.